Green infrastructure and urban revitalisation in Central Europe - Pichler-Milanović, Nataša (Urbani izziv, 2015)
The paper focuses on developing the green infrastructure concept in the emerging strategies of urban resilience and sustainability in response to the multiple challenges facing European cities, including Ljubljana, the capital of Slovenia. In this context resilience is concerned with politically challenging questions about assumptions of equilibrium and the ability of humans to control the environment. Urban resilience can provide a common framework for multidisciplinary action by municipalities and other stakeholders, highlighting the impact of planning urban eco-systems with the development of green infrastructure to meet environmental and spatial challenges. This paper identifies some of these strategies and activities in Ljubljana on the basis of research conducted under the EU FP7 TURAS project (2011-2016). In the inner-city neighbourhood of Tabor, there is already a broad range of collaborative planning and community participation activities (both top-down and bottom-up) towards developing (public and private) green infrastructure. This diverse locality has been identified as a %bridging% area where urban resiliency strategies for green infrastructure development are considered as a tool for implementing urban revitalisation projects in order to sustain viability and improve the quality of life for local residents and other citizens in times of limited financial resources. The research in Tabor shows that developing green infrastructure in keeping with the urban resilience concept is not sufficiently integrated in official spatial planning and municipal action due mainly to institutional and social obstacles.
Keywords: green infrastructure; Ljubljana; mesta; prenova; revitalisation; revitalizacija; spatial planning; Tabor neighbourhood; urban resilience